2021
DOI: 10.1002/bio.4033
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of silver and strontium oxide aluminate nanoparticles integrated into plasma‐activated cotton fabric: luminescence, superhydrophobicity, and antimicrobial activity

Abstract: Smart textiles with a multifunctional surface, such as with photoluminescence, antimicrobial, and superhydrophobic properties, are highly desirable. Silver nanoparticles (Ag NPs) were prepared and immobilized onto a cotton surface using a facile pad-dry-curing technique to introduce long-lasting antimicrobial properties. The morphology of the silver immobilized cotton fibres was explored using scanning electron microscopic images and energy-dispersive X-ray spectra. The morphology of the formed Ag NPs was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
23
1
Order By: Relevance
“…There have been very few studies on the production of long-persistent phosphorescent cotton fibres and other cellulose substrates reported by Khattab and coworkers. [59][60][61][62][63] However, the current study reported long-persistent and RTV-ASO-Ex-3 exhibited only fluorescence as they did not display any emissive bands after directly turning off the ultraviolet source. Therefore, only samples treated with an amount of ASO equal to or higher than RTV-ASO-3 were able to introduce long-lasting phosphorescence.…”
Section: Luminescence Propertiescontrasting
confidence: 59%
“…There have been very few studies on the production of long-persistent phosphorescent cotton fibres and other cellulose substrates reported by Khattab and coworkers. [59][60][61][62][63] However, the current study reported long-persistent and RTV-ASO-Ex-3 exhibited only fluorescence as they did not display any emissive bands after directly turning off the ultraviolet source. Therefore, only samples treated with an amount of ASO equal to or higher than RTV-ASO-3 were able to introduce long-lasting phosphorescence.…”
Section: Luminescence Propertiescontrasting
confidence: 59%
“…The photoluminescent pigment (SrAl 2 O 4 :Eu 2+ ,Dy 3+ ) was assembled using an earlier reported method. [ 48,60 ] An admixture of aluminum oxide (2 mol), europium oxide (Eu 2 O 3 ; 0.02 mol), strontium carbonate (1 mol), boric acid (0.2 mol) and dysprosium oxide (Dy 2 O 3 ; 0.03 mol), was subjected to dispersion in ethanol. The admixture was subjected to ultrasonic (30 kHz) for 30 min, heated at 90°C for over 24 h, and subjected to grinding in a planetary ball mill for 2 h. Under an atmosphere of a reduction carbon, the produced powder was exposed to sintering process at 1300°C for 3 h. The produced powder was exposed milling again and sieving to developed nanoparticles of the photoluminescent pigment (SrAl 2 O 4 :Eu 2+ ,Dy 3+ ) in the range of 7 to 12 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, SrAl 2 O 4 :Eu 2+ ,Dy 3+ is a highly valuable choice to provide fluorescent and photochromic authentication to documents without adversely influencing their inherent characteristics, such as mechanical properties, appearance and handling. [ 58–62 ]…”
Section: Introductionmentioning
confidence: 99%
“…No major effects were observed in the photoluminescence performance of the coated woods, which demonstrated optical activity almost identical to that of LASO NPs. [ 62 ]…”
Section: Resultsmentioning
confidence: 99%